2003
DOI: 10.3346/jkms.2003.18.4.520
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in Experimental Cerulein Induced Pancreatitis

Abstract: An enhanced formation of nitric oxide (NO), due to the induction of inducible nitric oxide synthase (iNOS), has been implicated in the pathogenesis of shock and inflammation, but its role in acute pancreatitis still remains controversial. To clarify the role of NO in acute pancreatitis, the present experiment investigated the expression of iNOS and the effect of NOS inhibition on cerulein-induced pancreatitis in rats. Group I received intraperitoneal (ip) injection of normal saline. Group II received two ip in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…As one of the important common mediators in inflammatory mediator cascade reaction of inflammatory reaction [15][16][17] , Nitric oxide (NO) can be regarded as an index of SAP. However, some researchers [18] believe that a small amount of endogenous NO can protect the body from ischemiareperfusion injury, and prevent any increase in intestinal vasopermeability induced by endotoxemia and bacteria translocation.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the important common mediators in inflammatory mediator cascade reaction of inflammatory reaction [15][16][17] , Nitric oxide (NO) can be regarded as an index of SAP. However, some researchers [18] believe that a small amount of endogenous NO can protect the body from ischemiareperfusion injury, and prevent any increase in intestinal vasopermeability induced by endotoxemia and bacteria translocation.…”
Section: Discussionmentioning
confidence: 99%
“…NO overproduction by iNOS in the pancreas is implicated in the exacerbation of cell injury during AP (Lomis et al 1995;Viola et al 2000;Ayub et al 2001;Simsek et al 2001;Cuzzocrea et al 2002;Ozturk et al 2003;Um et al 2003;Chen et al 2004;Isik et al 2004;Sandstrom et al 2005). One possible mechanism of NO-mediated damage is potentiation of oxidative stress by NO.…”
Section: Mechanisms Of Ros and Rns Induced Damage In Pancreatic Acinamentioning
confidence: 99%
“…It has been demonstrated that an enhanced formation of NO plays an important role in the pathogenesis of experimental acute pancreatitis, since NO synthase inhibition decreases the severity of pancreatitis [12,13] . In addition, excess of NO is an important factor underlying the systemic haemodynamic disturbance and oxidative tissue damage associated with acute pancreatitis [14] .…”
Section: Discussionmentioning
confidence: 99%